European Code against Cancer 4th Edition: Physical activity and cancer. (December 2015) - Leitzmann, Michael; Powers, Hilary; Anderson, Annie S.; Scoccianti, Chiara; Berrino, Franco; Boutron-Ruault, Marie-Christine; Cecchini, Michele; Espina, Carolina; Key, Timothy J.; Norat, Teresa; Wiseman, Martin; Romieu, Isabelle
Abstract: Physical activity is a complex, multidimensional behavior, the precise measurement of which is challenging in free-living individuals. Nonetheless, representative survey data show that 35% of the European adult population is physically inactive. Inadequate levels of physical activity are disconcerting given substantial epidemiologic evidence showing that physical activity is associated with decreased risks of colon, endometrial, and breast cancers. For example, insufficient physical activity levels are thought to cause 9% of breast cancer cases and 10% of colon cancer cases in Europe. By comparison, the evidence for a beneficial effect of physical activity is less consistent for cancers of the lung, pancreas, ovary, prostate, kidney, and stomach. The biologic pathways underlying the association between physical activity and cancer risk are incompletely defined, but potential etiologic pathways include insulin resistance, growth factors, adipocytokines, steroid hormones, and immune function. In recent years, sedentary behavior has emerged as a potential independent determinant of cancer risk. In cancer survivors, physical activity has shown positive effects on body composition, physical fitness, quality of life, anxiety, and self-esteem. Physical activity may also carry benefits regarding cancer survival, but more evidence linking increased physical activity to prolonged cancer survival is needed. Future studies using new technologies – such as accelerometers and e-tools – will contribute to improved assessments of physical activity. Such advancements in physical activity measurement will help clarify the relationship between physical activity and cancer risk and survival. Taking the overall existing evidence into account, the fourth edition of the European Code against Cancer recommends that people be physically active in everyday life and limit the time spent sitting.